Edukasi Peran Sanitasi Lingkungan Sehat Dalam Penurunan Risiko Stunting Di II Desa Sukasari Kec. Air Periukan Kab. Seluma - Pramesti, Stela; Hasanah, Jumrotul; Nurcahyanti, Heli; Kartika, Pila; Diniarti, Fiya; Surahman, Ferry (Utami Publisher, 2025)
Environmental sanitation is one of the essential aspects in achieving an optimal level of public health. Inadequate sanitation conditions can increase the risk of infectious diseases such as diarrhea, helminth infections, and other gastrointestinal illnesses, which directly affect children’s nutritional status. The imbalance between nutrient intake and recurring infections may lead to stunting in early childhood. This study aims to educate the community about the role of proper environmental sanitation in reducing the risk of stunting in Dusun II, Sukasari Village, Air Periukan Subdistrict, Seluma Regency. The method used in this activity was community outreach in the form of health education, involving 13 students from the Thematic Community Service Program (KKNT) and local village officials. The activities included delivering educational materials on environmental sanitation, waste management, and strategies for clean and healthy living. The results of this initiative showed a high level of community participation and an increased awareness of the importance of maintaining proper sanitation. It is expected that this educational effort will promote positive behavioral changes among the residents in maintaining a clean environment as a preventive strategy against stunting.